Asean Youth Center Di Pekanbaru Dengan Pendekatan Arsitektur Neo Vernacular - Ade Nofriansyah; Wahyu Hidayat; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Years of 2015, is a new era in ASEAN region, goes to compromise of ASEAN Economic Society (MEA). Every citizen in ASEAN region has equal opportunity in economic competition, without exceptionyouths. One of the most issues about youth is youth increasing ability program in ASEAN region. To reach this program, It needs a facility as container that known with youth center. Indonesia as country has mainly actor in increasing youthparticipation. It signs that Indonesian was being hosted some youth agendas. Therefore nowadays, Indonesia has not youth center facility that it can be container youth activity.Because of that it should produce youth center facility in Indonesia. Pekanbaru has wellchosen as location of youth center in Indonesia because it has strategic location, besides ofMalacca strait in which international trade routes and directly beside of some ASEAN country. ASEAN youth center perhaps afford to be ASEAN youth representative. Youth center in Pekanbaru emphasis is post-modern architecture, it means is combine modern style between vernacular architecture. It emphasis will produce modern shape but it still has local tradition or local genius. The aim of this research is designing ASEAN youth center inPekanbaru with Neo-Vernacular architecture as paradigm. Generally the strategy on this design such as zoning, mass shape, outdoor / landscape, circulation, structure, and facade.The result of this research is getting ASEAN youth center design in which combine some ASEAN architecture style like Malay, Hindu temple and Buddha temple.Keywords: ASEAN, Youth Center, Neo Vernacular, Pekanbaru.